Structure of the AcrAB-TolC multidrug efflux pump - Du, Dijun (Nature, 2014)
The capacity of numerous bacterial species to tolerate antibiotics and other toxic compounds arises in part from the activity of energy-dependent transporters. In Gram-negative bacteria, many of these transporters form multicomponent ‘pumps’ that span both inner and outer membranes and are driven energetically by a primary or secondary transporter component(1-7). A model system for such a pump is the acridine resistance complex of Escherichia coli(1). This pump assembly comprises the outer-membrane channel TolC, the secondary transporter AcrB located in the inner membrane, and the periplasmic AcrA, which bridges these two integral membrane proteins. The AcrAB-TolC efflux pump is able to vectorially transport a diverse array of compounds with little chemical similarity, and accordingly confers resistance to a broad spectrum of antibiotics. Homologous complexes are found in many Gram-negative species, including pathogens of animals and plants. Crystal structures are available for the individual pump components(2-7) and these have provided insights into substrate recognition, energy coupling and the transduction of conformational changes associated with the transport process. How the subunits are organised in the pump, their stoichiometry and the details of their interactions are not known and are under debate. In this manuscript, we present the pseudoatomic structure of a complete multidrug efflux pump in complex with a modulatory protein partner(8). The model defines the quaternary organization of the pump, identifies key domain interactions, and suggests a cooperative process for channel assembly and opening. These findings illuminate the basis for drug resistance in numerous pathogenic bacterial species.